Commercial real estate: global trends and methods of rating investment funds - Radenia, Aleksander M. (Journal of the Belarusian State University. Economics, 2023)
New trends in the global commercial real estate market are being identified and formalised. The investment process in the commercial real estate market and the special role of real estate investment funds in it are analysed. A methodology for rating such funds from the investor’s perspective is proposed.